Pengaruh Pemanfaatan Teknologi Informasi, Sistem Informasi Akuntansi Dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Bumdes Di Kecamatan Dawan - Ni Made Dwi Cahyani; I Putu Deddy Samtika Putra; Ni Ketut Muliati (UNHI Press, 2026)
The purpose of this study is to determine the effect of information technology utilization, accounting information systems, and human resource competence on the quality of BUMDes financial statements in Dawan District. The population in this study consisted of 107 BUMDes employees from 7 BUMDes. The sampling technique used was purposive sampling with a total sample of 41 respondents. This study used multiple linear regression analysis techniques with SPSS Version 24.0, including descriptive statistical tests, instrument tests, classical assumption tests, coefficient of determination (R2) tests, F-tests, and t-tests. The results of this study show that the utilization of information technology, accounting information systems, and human resource competence have a positive and significant effect on the quality of BUMDes financial statements in Dawan District.